If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -69 = -3x + 30 Reorder the terms: -69 + 6x = -3x + 30 Reorder the terms: -69 + 6x = 30 + -3x Solving -69 + 6x = 30 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -69 + 6x + 3x = 30 + -3x + 3x Combine like terms: 6x + 3x = 9x -69 + 9x = 30 + -3x + 3x Combine like terms: -3x + 3x = 0 -69 + 9x = 30 + 0 -69 + 9x = 30 Add '69' to each side of the equation. -69 + 69 + 9x = 30 + 69 Combine like terms: -69 + 69 = 0 0 + 9x = 30 + 69 9x = 30 + 69 Combine like terms: 30 + 69 = 99 9x = 99 Divide each side by '9'. x = 11 Simplifying x = 11
| x^2+31x+43= | | Y=60+5x | | 3x^2-24x-60=0 | | 6-x+4=19 | | x^2+12x=-25 | | x^4+7x^3+8x^2-7x+15=0 | | 12c^2+19x-21=0 | | 12x^2+25-7=0 | | 10n=109 | | 12*-1=y | | (x+6)(x+6)-11=0 | | 12-20y=20 | | (y-1)(y-1)=16 | | 3(p-1)=4(2p+7) | | 5(5+x)=3(x+7) | | 8+5x+6(10x)=608+5x | | 2x=52 | | 8y^2+22y-21= | | 2*x^2-2x-66=7 | | u^2=98 | | 2*x-66=7 | | 11x^2+7x=0 | | 3+5=z | | 67=(x)(.5x) | | (-2x^2+6x+1)-2(4x^2-3x+1)= | | n=.03x-58.19 | | 5xy+3x-2xy= | | 6+2x=30 | | 114x-227500=I | | 2x+3=2(x+3) | | -.9=.6x | | 6p+6=8+5p |